2014
DOI: 10.1038/leu.2014.93
|View full text |Cite
|
Sign up to set email alerts
|

Flavaglines target primitive leukemia cells and enhance anti-leukemia drug activity

Abstract: Identification of agents that target human leukemia stem cells (LSCs) is an important consideration for the development of new therapies. The present study demonstrates that rocaglamide and silvestrol, closely related natural products from the flavagline class of compounds, are able to preferentially kill functionally defined LSCs while sparing normal stem and progenitor cells. In addition to efficacy as single agents, flavaglines sensitize leukemia cells to several anti-cancer compounds, including front-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…This would also address the question of whether there are transcripts uniquely sensitive to silvestrol and not other translation initiation inhibitors. Consistent with this idea is a recent study reporting that silvestrol was a more potent cytotoxic reagent towards leukemia cells than the rapalog, temsirolimus [156].…”
Section: Rocaglatesmentioning
confidence: 58%
See 1 more Smart Citation
“…This would also address the question of whether there are transcripts uniquely sensitive to silvestrol and not other translation initiation inhibitors. Consistent with this idea is a recent study reporting that silvestrol was a more potent cytotoxic reagent towards leukemia cells than the rapalog, temsirolimus [156].…”
Section: Rocaglatesmentioning
confidence: 58%
“…In an investigation assessing the effects of silvestrol in a mouse hepatocellular carcinoma model, silvestrol was found to improve median survival in tumor-bearing mice without inducing damage to normal hepatocytes [148]. Along with solid tumors, several groups have shown that silvestrol is effective in the treatment of lymphomas and leukemia, with increased selectivity for malignant B cells compared to nontransformed T cells, suggesting that there may be a favorable therapeutic index for treatment of B cell malignancies [149,[155][156][157][158]. Moreover, silvestrol can re-sensitize chemoresistent B cell lymphomas to doxorubicin, suggesting a potential use in combination therapy [49].…”
Section: Rocaglatesmentioning
confidence: 98%
“…1A). RocA was shown to possess potent anticancer activity, but the connection to Fli-1 status is not known, nor do we fully understand its underlying mechanism [28][29][30]. A1544 and A1545 inhibited luciferase activity of FB-Luc driven by Fli-1 or EWS-FLI1 in a dose-dependent manner ( Fig.…”
Section: Identification Of Natural Anti-fli-1 Flavagline-like Compounmentioning
confidence: 99%
“…Recently, Roc‐A was also shown to sensitize leukemia cells toward anticancer compounds that have distinct actions, e.g . drugs that inactivate Bcl‐2 proteins, inhibit heat‐shock protein 90 or induce reactive oxygen species . Interestingly, Roc‐A showed a much stronger effect compared to Temsirolimus, a translation inhibitor that specifically inhibits mTOR.…”
Section: Therapeutic Aspects Of Rocs For Cancer Therapymentioning
confidence: 99%
“…drugs that inactivate Bcl-2 proteins, inhibit heat-shock protein 90 or induce reactive oxygen species. 78 Interestingly, Roc-A showed a much stronger effect compared to Temsirolimus, a translation inhibitor that specifically inhibits mTOR. This feature indicates that Rocs-mediated synergy may involve multiple mechanisms rather than only inhibition of general protein synthesis.…”
Section: Enhancing Efficacy Of Chemotherapymentioning
confidence: 99%